IMPLEMENTATION AND EFFECTIVENESS OF QUANTITATIVE RESEARCH METHODS IN ISLAMIC RELIGIOUS EDUCATION - Afif Agistiannur, Muhammad; Dina Hermina; Norlaila (As-Sulthan Journal of Education, 2025)
This study aims to analyze the implementation and effectiveness of quantitative research methods in the field of Islamic Religious Education (PAI). Quantitative research methods have been widely used to evaluate the learning process, curriculum effectiveness, and factors that influence PAI learning achievement. This article discusses the advantages, limitations, and recommendations for the application of this method in the context of PAI. The results show that quantitative research methods provide strong empirical data to support decision making in education. A descriptive analytical approach is used to analyze various literature that discusses the application of quantitative methods in the context of Islamic religious education. The research results show that this method is superior in producing measurable, accurate and generalizable data. Other advantages include the ability to systematically test hypotheses through statistical analysis. However, its limitations lie in its reliance on basic assumptions and lack of flexibility in understanding complex and dynamic phenomena. In the context of Islamic religious education, quantitative methods are very relevant for evaluating data-based policies and increasing the effectiveness of the learning process. This research recommends integrating quantitative methods with qualitative approaches to enrich understanding and provide more holistic results.